2019
DOI: 10.1556/2006.8.2019.24
|View full text |Cite
|
Sign up to set email alerts
|

Social media addiction and sexual dysfunction among Iranian women: The mediating role of intimacy and social support

Abstract: Background and aims: Social media use has become increasingly popular among Internet users. Given the widespread use of social media on smartphones, there is an increasing need for research examining the impact of the use of such technologies on sexual relationships and their constructs such as intimacy, satisfaction, and sexual function. However, little is known about the underlying mechanism why social media addiction impacts on sexual distress. This study investigated whether two constructs (intimacy and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 49 publications
4
23
0
2
Order By: Relevance
“…Process Marco (Alimoradi, Lin, Imani, Griffiths, & Pakpour, 2019; Hayes, 2103) in SPSS version 24.0 (IBM) was used to perform the mediation models. More specifically, Model 4 in Process Marco with 10,000 bootstrap samples was used to examine the mediated effects for each mediation model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Process Marco (Alimoradi, Lin, Imani, Griffiths, & Pakpour, 2019; Hayes, 2103) in SPSS version 24.0 (IBM) was used to perform the mediation models. More specifically, Model 4 in Process Marco with 10,000 bootstrap samples was used to examine the mediated effects for each mediation model.…”
Section: Methodsmentioning
confidence: 99%
“…In order to strengthen the rationale of the proposed direction, reverse mediation models (i.e., morningness/eveningness being the outcome variable; problematic social media use, anxiety, depression and daytime sleepiness being the independent variables) were additionally conducted. If the reverse models had poor results, the proposed direction was somewhat supported.Process Marco(Alimoradi, Lin, Imani, Griffiths, & Pakpour, 2019;Hayes, 2103) in SPSS version 24.0 (IBM) was used to perform the mediation models. More specifically, Model 4 in Process Marco with 10,000 bootstrap samples was used to examine the mediated effects for each mediation model.…”
mentioning
confidence: 99%
“…The 13 items are rated on a five-point Likert scale (ranging from 0 to 4), with higher scores indicating more sexual distress [22]. The FSDS has been translated into Persian with satisfactory internal consistency (α = 0.81) [23] and good known-group validity (i.e., the Persian FSDS can distinguish sexual distress among healthy women, women with hypoactive sexual desire disorder, and women with other types of female sexual dysfunction) [24].…”
Section: Female Sexual Distress Scale Revised Version (Fsds)mentioning
confidence: 99%
“…Previous studies have revealed the benefits of S-SMU among female. A study in married women found that couple's intimacy and perceived social support can decrease sexual distress (Alimoradi et al, 2019); Frison and Eggermont (2015) found that girls who actively use Facebook could benefit from perceive online social support, as it negatively predicted girls' depressed mood. However, teen girls also reported that social media would cause stress; those girls with high reliance on Facebook for emotional support had more negative school outcomes (Thompson & Lougheed, 2012).…”
Section: Discussionmentioning
confidence: 99%